2020
DOI: 10.1080/17470919.2019.1703807
|View full text |Cite
|
Sign up to set email alerts
|

Gender identity relevance predicts preferential neural processing of same-gendered faces

Abstract: The very early perceptional processes that underlie social categorization can be detected with event-related brain potentials (ERPs). Using this methodology, the present work aims to detect differential attentional processing of ingroup and outgroup members based on gender categories. Specifically, three EEG studies tested how factors that enhance social identity relevance, namely gender identification and contextual salience of gender representation, moderate neural gender categorization effects. Study 1 show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Especially people who strongly identify with their group are motivated to protect and improve their group’s image when under threat (Ellemers et al, 1997; Ouwerkerk et al, 2000). People who identify less strongly with their group are less concerned about their ingroup, less inclined to categorize themselves and others based on it (Domen et al, 2020), and tend to focus on their individual outcomes, even at the expense of their group (Ellemers et al, 1997).…”
Section: Men’s Responses To Gender Hierarchy Changesmentioning
confidence: 99%
“…Especially people who strongly identify with their group are motivated to protect and improve their group’s image when under threat (Ellemers et al, 1997; Ouwerkerk et al, 2000). People who identify less strongly with their group are less concerned about their ingroup, less inclined to categorize themselves and others based on it (Domen et al, 2020), and tend to focus on their individual outcomes, even at the expense of their group (Ellemers et al, 1997).…”
Section: Men’s Responses To Gender Hierarchy Changesmentioning
confidence: 99%
“…More recently, event-related potentials (ERPs) have been used to detect a neural categorization effect that responds to changes in contextual social identity salience (Domen, Derks, van Veelen, & Scheepers, 2020). However, neither the WSW paradigm nor ERPs can be used to study the dynamic aspects of social identity salience in real-world contexts.…”
Section: Indirect Measures Of Saliencementioning
confidence: 99%
“…Indeed, it has been widely shown that the degree of masculinity/femininity, rather than biological sex, is a better predictor of body perception and body satisfaction (Cella et al, 2013). Notably, a recent study showed that gender identification, more the biological sex, explains individual differences in autobiographical memory (Compère et al, 2021) and also modulates the initial perceptual processing responses of male and female observers to same vs. opposite gender faces (Domen et al, 2020). Accordingly, we entered as a predictor into a standard multiple regression analyses two partially independent measures of social autistic traits (i.e., Social skills and Communication; Austin, 2005) and a measure of cognitive autistic traits (i.e., Attention to details), the PST of the BUT, and the Masculinity and Femininity scores of the BSRI.…”
Section: Regression Analysismentioning
confidence: 99%
“…Indeed, it has been widely shown that the degree of masculinity/femininity, rather than biological sex, is a better predictor of body perception and body satisfaction (Cella et al, 2013 ). Notably, a recent study showed that gender identification, more the biological sex, explains individual differences in autobiographical memory (Compère et al, 2021 ) and also modulates the initial perceptual processing responses of male and female observers to same vs. opposite gender faces (Domen et al, 2020 ).…”
Section: Regression Analysismentioning
confidence: 99%